Enhanced structural maturation of human induced pluripotent stem cell-derived cardiomyocytes under a controlled microenvironment in a microfluidic system. (15th January 2020) - Kolanowski, Tomasz Jan; Busek, Mathias; Schubert, Mario; Dmitrieva, Anna; Binnewerg, Björn; Pöche, Jessie; Fisher, Konstanze; Schmieder, Florian; Grünzner, Stefan; Hansen, Sinah; Richter, Andreas; El-Armouche, Ali; et al.
Abstract: The lack of a fully developed human cardiac model in vitro hampers the progress of many biomedical research fields including pharmacology, developmental biology, and disease modeling. Currently, available methods may only differentiate human induced pluripotent stem cells (iPSCs) into immature cardiomyocytes. To achieve cardiomyocyte maturation, appropriate modulation of cellular microenvironment is needed. This study aims to optimize a microfluidic system that enhances maturation of human iPSC-derived cardiomyocytes (iPSC-CMs) through cyclic pulsatile hemodynamic forces. Human iPSC-CMs cultured in the microfluidic system show increased alignment and contractility and appear more rod-like shaped with increased cell size and increased sarcomere length when compared to static cultures. Increased complexity and density of the mitochondrial network in iPSC-CMs cultured in the microfluidic system are in line with expression of mitochondrial marker genes MT-CO1 and OPA1 . Moreover, the optimized microfluidic system is capable of stably maintaining controlled oxygen levels and inducing hypoxia, revealed by increased expression of HIF1α and EGLN2 as well as changes in contraction parameters in iPSC-CMs. In summary, this microfluidic system boosts the structural maturation of iPSC-CM culture and could serve as an advanced in vitro cardiac model for biomedical research in the future. Statement of Significance: The availability of in vitro human cardiomyocytes generated from induced pluripotent stem cells (iPSCs) opens the possibility to develop human in vitro heart models for disease modeling and drug testing. However, iPSC-derived cardiomyocytes remain structurally and functionally immature, which hinders their application. In this manuscript, we present an optimized and complete microfluidic system that enhances maturation of iPSC-derived cardiomyocytes through physiological cyclic pulsatile hemodynamic forces. Furthermore, we improved our microfluidic system by using a closed microfluidic recirculation and oxygen exchangers to achieve and maintain low oxygen in the culture chambers, which is suitable for mimicking the hypoxic condition and studying the pathophysiological mechanisms of human diseases in vitro . In the future, a variety of technologies including 3D tissue engineering could be integrated into our system, which may greatly extend the use of iPSC-derived cardiac models in drug development and disease modeling. Graphical abstract: Image, graphical abstract